Transformation of Family Support in Islamic Marriage in the Contemporary Era: A Critical Analysis of Sanad Hadith. - Kusmidi, Henderi; A. Suradi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to explore and analyze the transformation of the concept of family support in the context of Islamic marriage in the contemporary era. This research method includes analysis of hadith documents, interviews, and surveys to acquire a comprehensive understanding of the changes and dynamics that have occurred. The results show that this transformation includes shifts in values, gender roles, and economic demands that influence the view and implementation of family livelihoods. These challenges include economic equality between husband and wife, changes in traditional roles in the family, and adaptation to changes in the social environment. On the other hand, there are opportunities to strengthen gender equality values, increase understanding of the concept of livelihood, and develop more inclusive financial strategies. The implications of this research contribute to further understanding of how Islamic marriage adapts to changing times, as well as providing a basis for developing practical guidelines for husband-and-wife couples in managing family support in the contemporary era. This understanding can provide a more holistic and relevant view of the role of income in Islamic marriage amidst the dynamics of contemporary society.